Hubungan Tingkat Pengetahuan dan Nilai Budaya Ibu terhadap Pemberian ASI Eksklusif pada Balita Usia 07-59 Bulan di Wilayah Kerja UPTD Puskesmas Geureudong Pase Kabupaten Aceh Utara - Muslim Amin; Ahmad Fausi; Angga Afirza; Zul Rahmad; Syafiq Saputra Ariga; Anza Novaldi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The incidence of stunting in Indonesia is quite high compared to other countries. Meanwhile, the prevalence of stunting data at the Geureudong Pase Health Center, North Aceh Regency, in 2023 is around 0.05% (North Aceh Health Office 2023). This study is a correlative descriptive research using a cross sectional approach. Data analysis using univariate was carried out descriptively to describe Maternal Age, Education, Occupation, and Income/month presented in the frequency distribution table. Bivariate analysis in this study used the Chi Square Correlation Test with α = 0.05. The results showed that 25 respondents (73.5%) had less and less knowledge of exclusive breastfeeding, a small proportion of 4 respondents (44.4%) had low knowledge in the category of lack of exclusive breastfeeding. Meanwhile, the results of the chi square test obtained a p-value of 0.003 (<0.05). Of the total 27 respondents with positive cultural values, 24 respondents (88.9%) provided exclusive breastfeeding with a low value, while only 3 respondents (11.1%) provided exclusive breastfeeding with good value. This shows that the majority of respondents with positive cultural values still have a lack of knowledge or practice in exclusive breastfeeding. Of the total 7 respondents with negative cultural values, only 1 respondent (14.3%) provided exclusive breastfeeding with a low value, while 6 respondents (85.7%) provided exclusive breastfeeding with a good value. A p-value of 0.000 indicates that there is a statistically significant relationship between cultural values and exclusive breastfeeding. A small P-value (less than 0.05) means that we can reject the zero hypothesis (no relationship) and accept an alternative hypothesis (there is a relationship). This study shows a significant relationship between cultural values and exclusive breastfeeding in the UPTD Region of the Geureudong Pase Health Center, North Aceh Regency.